Theories of Affect and Concepts in Generic Skills Education : Adventurous Encounters. - Just, Edyta (Cambridge Scholars Publishing, 2017)
During the last few years, the concept of generic skills and competences has become widespread across universities. An introduction to generic competences is, as such, important because it enables redefinition of educational goals and may positively rearrange forms of interaction in classes. It also indicates that education should inspire students to develop and use critical and creative forms of thinking, feeling and doing. On the one hand, the need to promote generic skills can be seen as driven by neoliberal desire. On the other, however, generic competences can enable students to think, fe.